Perspektif Al-Qur’an Tentang Angin - Muslim Muslim (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2020)
Wind is an important element in life on earth, both human life, animals and plants. In the Koran, wind is mentioned with the word riih in the singular form and riyah in the plural form. Various types of wind are mentioned in the Quran, among others: 'Aqiim winds, Sharshar winds,' Ashif winds, Qashif winds, Thayyibah winds, and Sakinah winds. Meanwhile, Al Quran also explains about the functions of the wind, including: helping the pollination process, moving the clouds so that it rains, moving the clouds so that it rains to fertilize the land, the wind influences the formation of sea waves, and as a warning bearer of doom.